2012
DOI: 10.1097/jom.0b013e318244503c
|View full text |Cite
|
Sign up to set email alerts
|

Mortality From Cancer and Other Causes in an Italian Cohort of Male Rubber Tire Workers

Abstract: This study shows no excess cancer risk among male rubber tire workers employed after 1954.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Occupational exposure to aromatic amines has long been recognized a risk factor for bladder cancer (Negri et al, 1989;Kogevinas et al, 2003;Bosetti et al, 2005;Pira et al, 2010;Pira et al, 2012), accounting for up to 15% of cases in men from selected high-risk populations D'Avanzo et al, 1995). However, a selected number of occupations a priori deemed as being of high risk for bladder cancer showed only a moderate, nonsignificant excess risk, indicating that occupational exposures are not a major factor for bladder cancer in this, mainly rural, population.…”
Section: Discussionmentioning
confidence: 95%
“…Occupational exposure to aromatic amines has long been recognized a risk factor for bladder cancer (Negri et al, 1989;Kogevinas et al, 2003;Bosetti et al, 2005;Pira et al, 2010;Pira et al, 2012), accounting for up to 15% of cases in men from selected high-risk populations D'Avanzo et al, 1995). However, a selected number of occupations a priori deemed as being of high risk for bladder cancer showed only a moderate, nonsignificant excess risk, indicating that occupational exposures are not a major factor for bladder cancer in this, mainly rural, population.…”
Section: Discussionmentioning
confidence: 95%
“…Table summarizes 26 articles describing 26 mortality studies of 14 occupational cohorts involving 270,408 workers (range: 327‐40 867) . These mortality studies included workers from facilities in the United States ( n = 13), Germany (4), United Kingdom (4), Italy (2), Sweden (2), and one study included facilities from five European countries (Germany, Italy, Poland, Sweden, and United Kingdom).…”
Section: Resultsmentioning
confidence: 99%
“…Several other recent cohort studies of rubber workers performed in Germany, the United Kingdom, and Italy reported similar findings. 9395 It is unknown to what extent these recent studies were affected by the Healthy Worker Effect. For additional information on the lung cancer risk associated with rubber manufacturing, see http://monographs.iarc.fr/ENG/Monographs/vol100F/mono100F-36.pdf.…”
Section: Iarc Group 1 Lung Carcinogens: Occupations and Manufacturingmentioning
confidence: 99%